2014
DOI: 10.1681/asn.2013090967
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-Lysine Prevents Arterial Calcification in Adenine-Induced Uremic Rats

Abstract: Vascular calcification (VC) is a life-threatening complication of CKD. Severe protein restriction causes a shortage of essential amino acids, and exacerbates VC in rats. Therefore, we investigated the effects of dietary L-lysine, the first-limiting amino acid of cereal grains, on VC. Male Sprague-Dawley rats at age 13 weeks were divided randomly into four groups: low-protein (LP) diet (group LP), LP diet+adenine (group Ade), LP diet+adenine+glycine (group Gly) as a control amino acid group, and LP diet+adenine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…The degree of bone regeneration [21,87] and the pathological conditions of diseased bone including some types of osteoporosis [88][89][90], osteoarthritis [91], osteopetrosis [92], and cancer metastasis [83,84] were reported to be assessed using the degree of BAp orientation. For example, in the primary type osteoporosis induced by estrogen deficiency, the degree of BAp c-axis orientation both in the cortical and trabecular bone of lumber vertebrae increases along the craniocaudal axis in which principal stress is applied [88].…”
Section: Usefulness Of the Bap C-axis Orientation In Bone Assessmentmentioning
confidence: 99%
“…The degree of bone regeneration [21,87] and the pathological conditions of diseased bone including some types of osteoporosis [88][89][90], osteoarthritis [91], osteopetrosis [92], and cancer metastasis [83,84] were reported to be assessed using the degree of BAp orientation. For example, in the primary type osteoporosis induced by estrogen deficiency, the degree of BAp c-axis orientation both in the cortical and trabecular bone of lumber vertebrae increases along the craniocaudal axis in which principal stress is applied [88].…”
Section: Usefulness Of the Bap C-axis Orientation In Bone Assessmentmentioning
confidence: 99%
“…Dietary L-lysine, vitamin E, and iron effectively reduce vascular calcification in animal models [53,54]. …”
Section: Strategies To Reduce Vascular Calcification and Their Effectmentioning
confidence: 99%
“…In fact, we have already reported that alanine and proline inhibit apoptosis of cultured VSMCs, and that L-lysine supplementation almost completely ameliorated vascular calcification in vivo. 3 Phosphate-induced vascular calcification, especially in the uremic milieu, is thought to involve chondrogenic/ osteogenic transdifferentiation of VSMCs. This type of vascular calcification corresponds morphologically to medial calcification.…”
mentioning
confidence: 99%
“…Recently, the attention of several investigators has been drawn to control subclinical chronic inflammation (microinflammation) in the kidney, which probably plays a critical role in promoting progression of diabetic nephropathy. 1,2 In this regard, Awad et al 3 (this issue) report effectiveness of anti-tumor necrosis factor-α (anti-TNF-α) antibody in the amelioration of experimental diabetic nephropathy in Ins2 Akita diabetic mice. Likewise, they observed protection from streptozotocin-induced hyperglycemic renal injury in another mouse model deficient in macrophage-specific TNF-α (CD11b Cre /TNF-α Flox/Flox ).…”
mentioning
confidence: 99%